2009
DOI: 10.1007/s10895-009-0569-5
|View full text |Cite
|
Sign up to set email alerts
|

Laurdan Spectrum Decomposition as a Tool for the Analysis of Surface Bilayer Structure and Polarity: a Study with DMPG, Peptides and Cholesterol

Abstract: The highly hydrophobic fluorophore Laurdan (6-dodecanoyl-2-(dimethylaminonaphthalene)) has been widely used as a fluorescent probe to monitor lipid membranes. Actually, it monitors the structure and polarity of the bilayer surface, where its fluorescent moiety is supposed to reside. The present paper discusses the high sensitivity of Laurdan fluorescence through the decomposition of its emission spectrum into two Gaussian bands, which correspond to emissions from two different excited states, one more solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
2
26
0
4
Order By: Relevance
“…In each case, the GP value decreased continuously as a function of temperature above the main transition into the L α phase. These results are consistent with others reported previously for Laurdan [4,13,17,19], although this may be the first time that it has been shown that the phenomenon occurs even at temperatures more than 90°C above the melting temperature (open squares in Panel B, dipalmitoleoylphosphatidylcholine melting temperature = −36°C).…”
Section: Curve Fittingsupporting
confidence: 93%
See 2 more Smart Citations
“…In each case, the GP value decreased continuously as a function of temperature above the main transition into the L α phase. These results are consistent with others reported previously for Laurdan [4,13,17,19], although this may be the first time that it has been shown that the phenomenon occurs even at temperatures more than 90°C above the melting temperature (open squares in Panel B, dipalmitoleoylphosphatidylcholine melting temperature = −36°C).…”
Section: Curve Fittingsupporting
confidence: 93%
“…Studies of either saturated phosphatidylcholine or phosphatidylglycerol consistently show a steady increase of apparent membrane polarity (i.e. decreased GP value or stronger solvent relaxation) as a function of temperature well above the lipid melting point [4,13,19].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is a wealth of studies on model membranes30313233343536 and an emerging literature12363738 on the use of dynamic imaging approaches to measure spectral relaxation in living cells. At the time this work was being completed, the Gratton laboratory12 published a phasor-based approach to measure membrane polarity and microviscosity.…”
Section: Discussionmentioning
confidence: 99%
“…In a lipid bilayer, this amphiphilic fluorophore is localized at the level of the glycerol backbone, with lauric acid tail anchored in the acyl chain region. Laurdan's emission spectrum has two clearly distinct components that are attributed to solvent-unrelaxed (shorter-wavelength band centered circa 440 nm) and solvent-relaxed states (longer-wavelength band centered circa 490 nm) (Lúcio et al 2010;Sanchez et al 2012). This photophysical property is thought to originate from the reorientation of water dipoles around the excited-state dipole of the probe molecule.…”
Section: Effects Of Protein Fibrils and Oligomers On The Membrane Strmentioning
confidence: 99%